PERLINDUNGAN HUKUM TERHADAP PERKAWINAN BELUM DICATATKAN BERBASIS MAQASHIDU AL-SYARIAH - Iskak Sulistiya; Absori Absori; Syaifuddin Zuhdi (Yayasan Merassa Indonesia Publikasi, 2026)
Unregistered marriage remains a family law problem in Indonesia because it creates a gap between religious validity and formal state recognition. This condition has a direct impact on the weak legal protection for women and children, particularly in fulfilling the rights to maintenance, joint property, inheritance, lineage, legal identity, and access to population documents. This study aims to analyze the forms of legal protection for women and children in unregistered marriages and to formulate a construction of legal protection based on Maqashidu al-Syariah. This study employs a normative legal research method with a statutory approach, a conceptual approach, and a maqashidi approach. Legal materials are analyzed qualitatively through descriptive-analytical and prescriptive techniques. The results show that the state has provided several forms of legal protection, namely preventive protection through the obligation of marriage registration, administrative protection through the inclusion of the status